Evolutionary and Ecological Explanations for the Elevational Flexibility of Several East African Bird Species Complexes - Fjeldså, Jon; Bowie, Rauri C. K. (Frontiers in Ecology and Evolution, 2021)
Africa’s montane areas are broken up into several large and small units, each isolated as forest-capped “sky islands” in a “sea” of dry lowland savanna. Many elements of their biota, including montane forest birds, are shared across several disjunct mountains, yet it has been difficult to rigorously define an Afromontane forest avifauna, or determine its evolutionary relationships with the birds of the surrounding lowland forests. In order to trace the historical relationship between lowland and highland avifaunas, we review cases of species or groups of closely related species with breeding populations at different elevations, and use phylogeographic methods to explore the historical connections between such populations within the biodiversity hotspot of East Africa. The study reveals several idiosyncratic patterns, but also a prominent number of cases of gene flow between populations in southern areas, mainly around the Malawi Rift, and mountains and coastal forests to the north, close to the equator. This may reflect more continuous past distributions through northern Mozambique and coastal Tanzania, or seasonal migrations between areas with different rainfall regimes. Over time, these distributional dynamics have resulted in a higher persistence of lineages, and an accumulation of forest-dependent lineages within the Eastern Arc Mountains of Tanzania and the northern part of the coastal forest mosaic.